Association of Fatigue With Sleep Duration and Bedtime During the Third Trimester - Ma, Duo; Kang, Yimin; Wang, Denglan; Chen, Haoxiong; Shan, Ligang; Song, Chun; Liu, Yanlong; Wang, Fan; Li, Hui (Frontiers in Psychiatry, 2022)
Purpose To investigate the association between fatigue and sleep habits of pregnant women to further explore the effect of sleep duration and bedtime on fatigue during the third trimester. Materials and Methods A total of 465 Chinese Han pregnant women in the third trimester (after 28 weeks) with a singleton gestation were recruited. Sleep habits (such as bedtime, sleep onset latency, and night sleep duration) and the 14-item Fatigue Scale scores (FS-14, used to assess fatigue) were collected. Results The effects of sleep duration and bedtime on FS-14 physical and total scores were significant. FS-14 physical scores and total scores of the participants in the group of sleep before 23 o’clock (SBC) of short sleep duration (<7 h) were significantly higher as compared to the participants in the group of SBC of normal sleep duration, and those of the participants in the group of SBC of normal sleep duration were significantly lower than the participants in the group of sleep after 23 o’clock of normal sleep duration. There were negative correlations of sleep duration with FS-14 physical score and total score in the SBC of short sleep duration group. Conclusion Sleep less than 7 h or bedtime after 23 o’clock was associated with increased fatigue levels of pregnant women in the third trimester. Therefore, it is necessary to develop good sleep habits (enough sleep duration and early bedtime) to keep fatigue at a low level for pregnant women in the third trimester.